2018
DOI: 10.7755/fb.116.3-4.5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution of late larval and juvenile rockfish (Sebastes spp.) and associated environmental conditions off Oregon and Washington: new insights based on genetics

Abstract: Abstract-Surveys of juvenile and larval stages can be useful for management of commercially important marine fishes but require definitive species identification. From May through October 2005October -2008 trawls collected 78,407 late-larval and juvenile rockfish (Sebastes spp.) in shelf and slope waters off Oregon and Washington. Because of their small size and lack of pigmentation, we could identify only 4.1% (3266 individuals) of sampled rockfishes to species morphologically, representing a total of 17 spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The timing of rockfish recruitment is very seasonal, particularly for the more northerly winter spawning species, and the survey was originally designed to include the time of peak abundance levels of these species in Central California [ 14 ]. More recently, based on monthly trawl sampling with a different gear type [ 57 ] confirmed that in the waters off of Oregon and Washington, the May-June period was most important for the larger commercially important species (e.g., widow, canary, and yellowtail rockfishes) while the later summer was characterized by higher catches of forage species. Despite this general finding, interannual differences in parturition times and growth rates could shift the availability of some species within this sampling window [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The timing of rockfish recruitment is very seasonal, particularly for the more northerly winter spawning species, and the survey was originally designed to include the time of peak abundance levels of these species in Central California [ 14 ]. More recently, based on monthly trawl sampling with a different gear type [ 57 ] confirmed that in the waters off of Oregon and Washington, the May-June period was most important for the larger commercially important species (e.g., widow, canary, and yellowtail rockfishes) while the later summer was characterized by higher catches of forage species. Despite this general finding, interannual differences in parturition times and growth rates could shift the availability of some species within this sampling window [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because it is difficult to visually distinguish many rockfish species when they are small, we categorized juvenile rockfishes into 5 groups established in the literature (Johansson et al 2018, Markel & Shurin 2020. ( 1) Yellowtail and black (YTB) included both yellowtail S. flavidus and black S. melanops rockfishes.…”
Section: Survey Designmentioning
confidence: 99%
“…First, trawling for samples both destroys the habitat (Hourigan, 2009;Clark et al, 2016) and integrates catches over large distances, making fine-scale associations difficult to determine. Second, identification of the early life stages of rockfishes is difficult prior to development of distinguishing characteristics (Matarese et al, 1989;Johansson et al, 2018).…”
mentioning
confidence: 99%